Structural, electronic and optoelectronic characteristics by first principles calculations for CH3NH3PbBr3 hybrid perovskite - Meena, A.; Bairwa, J. K.; Kumari, S.; Rani, U.; Kamlesh, P. K.; Singh, A. P.; Verma, Ajay Singh (Physics and Chemistry of Solid State, 2025)
Employing the Wien2k code, first-principles calculations within the full potential linearized augmented plane wave (FP-LAPW) method and density functional theory (DFT) framework were utilized to determine lattice constants, interatomic distances, density of states, and band structures. Three different exchange-correlation potentials, PBE, Local Density Approximation (“LDA”), and Wo-Cohen Generalized Gradient Approximation (“WC-GGA”), were employed for evaluating structural and electronic properties. The computed lattice constants and bulk modulus were found to be in excellent agreement with experimental data, validating the accuracy of the computational approach. The Goldsmith tolerance factor and octahedral factor were computed to confirm the structural stability of the material. The direct energy band gap of 2.32 eV observed at the R-R point suggests favourable conditions for solar applications. Further improvement in the band gap was achieved using the mBJ method. The optical properties, including the dielectric function, index of refraction, extinction coefficient, absorption coefficient, reflectivity, electron energy loss function, and photoconductivity, were systematically analysed. Notably, the study reveals the reliability of CH3NH3PbBr3 as an absorption layer in solar cells, supported by the enhanced band gap and other optical properties.